The Exodus of Filipino Teachers to Uzbekistan: A Hermeneutic Phenomenological Study - Pacala, Frank Angelo (Makara Human Behavior Studies in Asia, 2024)
Filipino teachers drawn to Uzbekistan were attracted by the prestige and mission of its government schools, bringing world-class teaching experience from numerous countries. This departure of Filipino teachers to Uzbekistan is the focus of a hermeneutic phenomenological study that discloses a valuable tapestry of themes that capture the intricate quality of the educators’ journey. The Filipino teachers who joined this study were employed for a minimum of two years. This study was performed through semi structured interviews, and the data went through structural, thematic analysis, exposing a narrative covering distinct themes. First, the resilience and adaptability of the international educators and the empowerment of the local teachers within the distinctive educational landscape were revealed. Second, the personal dimensions, covering gratitude for their roles, high regard for Filipinos, and living in a peaceful community while embracing simplicity and local culture, were explored by the theme. Third, the strategic motives were showcased, stressing compensation packages, student attitudes, and alignment with the institution's prestige. This study deepens our knowledge of the experiences of international educators, accentuating the intricacies of cross-cultural teaching. The educators’ dedication to efficient teaching programs and an active learning environment, as exhibited in their strategies for maintaining connections and comfort, adds meaningful insights to the broader discourse on global education.